Perfil de saúde e bem-estar subjetivo de um grupo de idosos praticantes de exercício físico em uma universidade pública no interior do Amazonas - Oliveira, Diego Castro de (Brasil, 2021)
The health profile and subjective well-being of elderly people who are part of a physical exercise group in a public university in the interior of Amazonas were traced. This is a descriptive, cross-sectional observational study, the sample consisted of 26 elderly people, there was a predominance of women aged between 60 and 69 years, with less than five years of education, retired, living with a spouse and using two to four medications. As for health conditions, the most prevalent diseases were hypertension, gastrointestinal diseases and osteoporosis. When evaluating the subjective well-being, most elderly people had a positive status when comparing their health with that of other people of the same age, as for the social support received, most elderly people had a negative status and said they needed a lot of help when they stay sick or need to make a decision, even financial help. The findings showed that chronic diseases and other health problems found in most elderly people are related to the socio-economic profile, eating habits and low level of physical activity, indicating that it is necessary to apply this study in a larger population of elderly people so that these results can be generalized.